A Clean Public Procurement System through Commitment Making Officials (PPK) Criminal Liability Reforms - Umar Maksum; Ade Saptomo (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
This research aims to explore a clean public procurement system through criminal liability reform for Commitment Making Officials (PPK). PPK plays an important role in maintaining accountability, transparency, and integrity in the public procurement process. The research method used is a statutory approach and a conceptual approach. This research analyzes the regulations governing PPK's responsibilities and how they can be held criminally liable if proven to have abused their authority. It was found that PPK is often the party fully responsible for irregularities in procurement, despite the important role of other parties such as the Budget User (PA) and the Budget User Authority (KPA). This research shows that to prevent corrupt practices, stricter monitoring mechanisms and increased legal awareness among PPKs are needed. Criminal liability reform for PPKs is essential to create a more transparent and accountable public procurement of goods and services. Better understanding of legal responsibilities and training for PVRs can reduce the risk of abuse of authority. Achieving a clean procurement system requires improvements in regulation and oversight, as well as capacity building for PVRs. These reforms will support corruption prevention efforts and maximize benefits for society and the state.